Re-deployment training - experiences and achievements - Sharma, N.N.; Agarwal, Neeraj (2000)
In a growing fast-changing technology and competitive, environment, training is considered an important activity in the Textile Industry. Still, very little attention is paid to Redeployment training activity, whereas modernisation and upgradation of technology does take place in textile mills. This paper deals with training approaches adopted during redeployment training, as also resuslts achieved through training. - Reproduced
Keywords: Training